2018
DOI: 10.29089/2017.17.00029
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of air pulsed cryotherapy on delayed onset muscle soreness of elbow flexors following eccentric exercise

Abstract: Effectiveness of air pulsed cryotherapy on delayed onset muscle soreness of elbow flexors following eccentric exercise article info A r t i c l e h i s t o r y Ke y w o r d s Delayed onset muscle soreness Air pulsed cryotherapy Eccentric exercise D o i 10.29089/2017.17.00029 U s e r l i c e n s e This work is licensed under a Creative Commons Attribution -NonCommercial -NoDerivatives 4.0 International License. abstract I n t r o d u c t i o n : Cryotherapy is widely used in sports to facilitate recovery from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The frequency and duration of cold therapy were cited as reasons for the lack of preventive effects against DOMS. Doungkulsa et al [ 16 ] reported that air-pulse cryotherapy (−30 °C) was performed for five consecutive days at 20-min sessions (four sessions × 5 min) after DOMS induction on the elbow flexor muscles. The results indicated a significant improvement air-pulse cryotherapy group in SOR-st, PPT, and upper arm circumference compared with the CONT group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The frequency and duration of cold therapy were cited as reasons for the lack of preventive effects against DOMS. Doungkulsa et al [ 16 ] reported that air-pulse cryotherapy (−30 °C) was performed for five consecutive days at 20-min sessions (four sessions × 5 min) after DOMS induction on the elbow flexor muscles. The results indicated a significant improvement air-pulse cryotherapy group in SOR-st, PPT, and upper arm circumference compared with the CONT group.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies [ 16 , 21 ], ROM was measured using a goniometer in the back-lying position in an anatomically correct posture, and joint angles were measured from the relaxed position with the arms along the body to the maximum extension position. Measurements were taken before and after the muscle damage protocol and on days 1–4 and 7 after the muscle damage protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations